“You Think You’re the Only One”: Comparing Descriptions and Lived Experiences of Polycystic Ovarian Syndrome - Vleming, Kaitlyn (Anthropologica, 2018)
This article examines the biomedical diagnosis of polycystic ovarian syndrome (PCOS) from the perspectives of medical anthropology and science and technology studies (STS), addressing two main questions: what does a historical, medical anthropology and STS perspective reveal about how PCOS is described and understood in contemporary North America, and what are the lived experiences of people with this diagnosis? Common descriptions of PCOS are based in normative gendered assumptions. Drawing on interviews with people diagnosed with PCOS and on analysis of historical and contemporary biomedical literature discussing PCOS, I argue that the lived experiences of people with PCOS vary significantly from mainstream (biomedical and popular) descriptions of the diagnosis.